Interaction of Cyprinus carpio Linnaeus with the biofilm-forming Aeromonas hydrophila - Ekaterina Lenchenko; Svyatoslav Lenchenko; Nadezhda Sachivkina; Olga Kuznetsova; Alfia Ibragimova (Veterinary World, 2022)
Background and Aim: The resistance of susceptible fish populations and the adaptive potential of heterogeneous biofilms, which cause multiple antibacterial resistance and long-term persistence of microorganisms, mediate the development and outcome of the infectious process. The study of the fish immunological parameters in interaction with biofilm-forming bacteria is of practical importance for assessing the stability of the homeostasis of the fish. This study aimed to determine the immunobiological parameters of Cyprinus carpio Linnaeus when interacting with biofilm-forming bacteria Aeromonas hydrophila.